Factors that Influence Fraudulent Financial Statements in Retail Companies - Indonesia - Rian Ferdinand; Setyarini Santosa (President University Press, 2018)
Fraudulent financial statements is an intentionally misstatement of the financial statements. There are several factors affected the evidence of fraudulent financial statements report. The objective of this research is to investigate the influence of audit committee characteristics, managerial ownership, leverage, and liquidity toward the fraudulent financial statements report in retail companies listed on the Indonesia Stock Exchange in the period of 2012-2016. Using regression, the result shows that audit committee characteristic and leverage do not have significant effect on the fraudulent financial statements report, while managerial ownership and liquidity have. Simultaneously, audit committee characteristics, managerial ownership, leverage and liquidity have significant influence to the fraudulent financial statement report.